RANCANG BANGUN ARSITEKTUR ENTERPRISE MENGGUNAKAN TOGAF PADA SISTEM ADMINISTRASI SURAT MENYURAT DI POLDA XYZ - Saputra, Joneten; Shandy; Prawinnetou, Wassy; Rahman, Abdul; Wahyu Sudrajat, Antonius (Jurnal Ilmiah Informatika Global, 2025)
In today's era, advancements in information technology (IT) are driving digital transformation across various sectors, including government institutions such as Polda Xyz. A key element of this transformation is the administrative correspondence system, which must be managed efficiently, structurally, and securely. This study aims to design an enterprise architecture that serves as the foundation for the comprehensive and integrated development of information systems, using the TOGAF (The Open Group Architecture Framework) methodology. This approach addresses challenges such as process inefficiencies, lack of integration between work units, and weak information security. By applying TOGAF through the Architecture Development Method (ADM), the proposed architecture encompasses four core domains: Business Architecture, Application Architecture, Data Architecture, and Technology Architecture. This research adopts a qualitative approach through literature studies, observations, interviews, and data analysis. The results produce an enterprise architecture blueprint and an implementation roadmap for the E-Office system, which are expected to enhance operational efficiency, communication effectiveness, and data security within Polda Xyz.